THE INFLUENCE OF PH ON THE KINETICS, REVERSIBILITY AND MECHANISMS OF PB(II) SORPTION AT THE CALCITE-WATER INTERFACE - Rouff A.A.; Elzinga E.J.; Reeder R.J.; Fisher N.S. (My University, 2005)
Pb(II) sorption experiments with calcite powders were conducted in suspensions equilibrated at atmospheric PCO2(g) and ambient temperature at pH 7.3, 8.2 and 9.4. Pb fractional sorption was low at pH 7.3 and 9.4 relative to pH 8.2, and correlated well with PbCO30(aq) speciation. Desorption experiments conducted for initial sorption times ranging from 0.5 h to 12 d reveal an almost completely reversible process at pH 8.2, attributed to the dominance of an adsorption mechanism, with slight and pronounced irreversibility at pH 7.3 and 9.4 respectively. Similarities in X-ray absorption near edge spectra (XANES) for 24 h and 12 d pH 7.3 and 9.4 sorption samples indicate no effect of initial sorption time. Results from linear combination (LC) fits of XANES spectra for samples sorbed at pH 9.4 confirm ∼75% adsorbed and ∼25% coprecipitated components. The coprecipitated fraction was attributed to the non-exchangeable metal observed in desorption experiments. At pH 7.3, ∼95% adsorbed and ∼5% coprecipitated components were obtained. A comparison of results from desorption experiments and LC-XANES alludes to an irreversibly bound adsorbed component for the pH 9.4 12 d sorption sample. Extended X-ray absorption fine structure spectroscopy (EXAFS) analysis of pH 7.3 and 9.4 12 d sorption samples confirms the presence of both adsorbed and coprecipitated metal. At pH 7.3 a first-shell Pb-O bond length of 2.38 Å is intermediate between that of adsorbed (2.34 Å) and coprecipitated (2.51 Å) Pb. At pH 9.4, two first-shell Pb-O distances at 2.35 Å and 2.51 Å were obtained, indicative of the occurrence of both adsorption and coprecipitation and a larger coprecipitated fraction relative to that at pH 7.3, consistent with LC-XANES results. We propose that the disparity in the fraction of coprecipitated metal with pH may be linked to the ability of sorbed Pb to inhibit near-surface dynamic exchange of Ca and CO3 species, which dictates step advance and retreat. Less effective inhibition of step motion at pH 9.4, due to lower fractional sorption, combined with highest rates of dynamic exchange results in a significant fraction of coprecipitated Pb at this pH. At low pH, though fractional sorption is also low, lower rates of exchange prohibit significant coprecipitation. At pH 8.2, effective inhibition of surface processes due to higher fractional sorption and lower rates of exchange compared to pH 7.3 and 9.4 preclude detectable coprecipitation. Other factors such as changes in surface speciation and solubility of the Pb-Ca solid solution with pH may also come into play. Overall, this study presents evidence for the influence of pH on Pb sorption mechanisms, and addresses the efficiency of Pb immobilization in calcitic systems.